THE IMPACT OF ACCOUNTING INFORMATION SYSTEMS ON FINANCIAL PERFORMANCE WITH THE ROLE OF SENIOR MANAGEMENT AS AN INTERVENING VARIABLE IN IRAQI INDUSTRIAL COMPANIES - Sattar Oleiwi Dahash (Scholar Express Journals, 2024)
This research aims to examine the impact of Accounting Information Systems (AIS) on financial performance in selected Iraqi industrial companies, specifically Baghdad Soft Drinks Company, UR State Company, and Wasit Textile Factory, with a focus on the role of senior management as a mediating variable that either strengthens or weakens this impact. Data was collected through a survey distributed to 100 financial managers and department heads in Iraqi industrial companies. The survey covered three main areas: accounting information systems, the role of senior management, and the financial performance of companies. The likert scale was used to analyze the responses and draw conclusions
Keywords: Accounting Information Systems; senior management; Financial Performance